Labour market modelling in the Czech Republic - Stoklasová, Radmila (Univerzita Pardubice, 2015)
The article deals with labour market modelling in the Czech Republic using regression model. The regression equation shows the behaviour of the unsatisfied labour supply determined by education and age structure of the unemployed, registered length of unemployment, available jobs average wage. In the second part of article is used prediction by Box-Jenkinson methodology. On the basis of the verified model a prediction for the first quarter year of 2015 is worked out and its success assessed. Population ageing will considerably influence economic and social structure of the population. The labour market will change completely. The future development of labour market will face a challenge of reduction of the negative initial demographic conditions. The main problem of the labour market in the Czech Republic is the exclusion of all groups of population due to the lack of flexible jobs, mainly part-time jobs (for example students, mothers with children and elderly people).
Keywords: labour market modeling; labour market supply; regression model; correlation analysis; Box-Jenkinson methodology; C32; C51